Rancang Bangun Aplikasi Knowledge Management Berbasis Web - Yance Sonatha; Indri Rahmayuni; Alde Alanda; Iswandi Saputra (Universitas Negeri Padang, 2018)
Knowledge management is an organization of knowledge held by individuals within an organization. With knowledge management,an individual knowledge can be own by organization so it can give a benefit to organization in order to enhance business competitiveness.Management and documentation of the knowledge in order to become a reference for all the employee within the organization are need a development and implementation of appropriate knowledge management system. The implementation of knowledge management system must be supported by specific features to store and organize the existing knowledge.To overcome this problem, a knowledge management system was designed in the form of a web-based programming system using PHP programming languages ​​with GTFW and MySQL Framework. Knowledge management systems are equiped with data search facilities, documentation and records of problems, information and download features from each of available documents.